Games of Enunciation in William Kentridge’s "Triumphs and Laments" - Pezzini, Isabella (E|C, 2020)
The peculiarities of the “Triumphs and Laments” make it a text of great interest from the point of view of visual enunciation, a field of theoretical reflection and analysis of devices that is increasingly central to the semiotic debate: here we will try to offer some elements.